The conjoined parascapular and latissimus dorsi free flap for reconstruction of extensive knee defects - Bigdeli, Amir Khosrow; Thomas, Benjamin; Schmidt, Volker-Jürgen; Hernekamp, Jochen-Frederick; Hirche, Christoph (Microsurgery, 2018)
Background Extensive soft-tissue defects affecting the knee region pose a significant reconstructive challenge and may require separate or multiple flaps for coverage. We evaluated the conjoined parascapular and latissimus dorsi free flap as an alternative reconstructive option. Methods From January 2013 to December 15, 2016 patients (7 female and 8 male) with a mean age of 47.5 years underwent reconstruction of such defects. Causes were trauma (12 cases) and infection (3 cases). The mean defect size was 40.9 × 20.8 cm (range, 21.4×7.3 to 60.1×40.5 cm). The mean defect surface area was 820.0 cm2 (range, 273.2-2,400.4 cm2). The conjoined free flap was anastomosed to the femoral vessels in the adductor canal with (3 cases) or without an arterio-venous loop (8 cases), posterior tibial vessels (3 cases), or anterior tibial vessels (1 case). Results Postoperatively, 10 patients experienced a total of 14 complications, of which 9 (7 patients) were considered major (requiring additional surgery) and 5 (4 patients) minor (conservative treatment). There was no total flap loss. Partial flap loss occurred in 5 patients. Major donor-site complications occurred in 6 patients with impaired wound healing (4 cases), seroma (1 case), and hematoma (1 case). Reconstruction was successful in 14 out of 15 patients during a mean follow-up time of 28.6 months (range, 6.0-52.5 months). Twelve patients were able to walk at the last follow-up visit. Conclusions The conjoined parascapular and latissimus dorsi free flap is a large and reliable flap. It allows for simultaneous 1-stage reconstruction of complex and unusually large soft-tissue defects of the knee region.